Responses of Musa AAA Berangan to 1-methylcyclopropene - Ding, Phebe; Darduri, Khairul Bariah (Universiti Putra Malaysia Press, 2009)
1-methylcyclopropene (1-MCP) is an inhibitor of ethylene perception and has been shown to delay the ripening of Cavendish bananas. Nevertheless, no work has reported the delay in the ripening of local bananas using 1-MCP. The objective of this study was to examine the responses of Berangan banana to 1-MCP applied at the ripening stage 1 (mature green) and ripening stage 2 (partially ripe In Experiment I,1 μL L-1 of 1-MCP was applied to mature green stage banana for 0, 2, 4 and 6 h, followed by ripening initiation using 10 g CaC2 kg-1 fruit for 24 h. Meanwhile, in Experiment II, the fruits were partially ripened using 10 g CaC2 kg-1 fruit for 24 h, followed by exposing them to 1 μL L-1 of 1-MCP for 0, 2, 4 and 6 h. Exposing mature green Berangan banana to 4 h of 1-MCP delayed degreening, retained flesh firmness and soluble solids concentration. On the contrary, exposing 1-MCP to the partially ripened banana fruit failed to delay both degreening and ripening processes. Fruit of both experiments ripened normally after the 1-MCP treatment, with more rapid ripening processes in partially ripe than mature green fruit.